PERANCANGAN FASILITAS KERJA UNTUK PENGANGKATAN BARANG BOX MINUMAN DI CV. CAHAYA BARU GEMILANG - Syahril, Ahmat; Zetli, Sri (LPPM Universitas Putera Batam, 2022)
In all industrial activities, the role of humans as a source of labor remains dominant. Unlike cars that can be repaired and replaced. Whoever is an employee still has limitations. In manual labor, people are at a greater risk of contracting MSD, which can lead to unsafe working conditions. Practice lifting a drink box in your CV. The AUDIO NEW LIGHT can be dangerous when lifting drawers due to manual and unsanitary working positions. The study has an average REBA occupational risk score of 8 in the high category for neck, back, waist, larynx, thigh, left arm, left and right wrist, right, indicating that immediate action is required. An approach to avoiding these risks when designing trolleys is to use EFD technology based on ENASE ergonomic considerations. The trolley element to reduce operator discomfort with its weight (0.306) is the highest priority in product development acquired by Efd, and above all, the target specification of the trolley created according to the anthropometric measurement of the operator is the highest priority for production. function. shoulder width (LB, Standing elbow height (TSB), and handlebar width are anthropometric data used for design (GT).